Online Teaching-Learning in Higher Education during Lockdown Period of COVID-19 Pandemic in India - Kaushik Das; Piashi Das (Research Parks Publishing LLC, 2020)
In India, educational institutions (schools, colleges and universities) are presently focused primarily on formal learning strategies, that is, adopting the traditional framework of face-to - face traditional classrooms. To determine the effect of the COVID-19 lockdown on bachelor's degree learners with different Indian colleges and universities. During that same pandemic, students from rural regions and marginalized areas primarily face immense technical challenges. Therefore, the analysis of these phenomena in the population of India is significant. This paper illustrates the effects of the middle flu outbreak on the Indian education sector and also points to some fruitful recommendations for carrying out educational activities during the pandemic situation. In addition, the role of teachers and the access to infrastructure for online education are identified. Qualitative methodology is a technique used for this study. This research involved the study of foreign and national publications, correspondence with the library, professional opinion, journal articles, newsletters, and records.